Laparoscopically assisted suprapubic surgery for adnexal tumors under epidural anesthesia. Issue 1 (2nd January 2017) - Kim, Ki Hyung; Kim, Yoon Hwa; Yun, Ka Yeong; Han, Si Eun; Kim, Eun Soo; Kwon, Byung Su; Suh, Dong Soo
Abstract: Objective: To evaluate the feasibility and safety of laparoscopically assisted surgery for benign ovarian tumors via a single suprapubic incision under epidural anesthesia. Methods: Forty-three patients underwent laparoscopically assisted surgery via a single suprapubic incision under epidural anesthesia. Types of surgery were classified as follows: type I – suprapubic incision surgery without laparoscopic support, type II – suprapubic incision surgery with laparoscopic support but without CO2 inflation; and type III – suprapubic incision surgery with laparoscopic support and CO2 inflation. Results: Type I, II, and III procedures were performed on 16, 21, and six patients, respectively. Most patients (n = 35) were discharged on postoperative day 1 or 2. No surgical complication was encountered. Types of surgery exhibited different surgical characteristics. Type I was adopted for larger diameter tumors than types II or III (p = .016), whereas type III had a longer operative time (p = .024) than types I and II. Other characteristics, such as age, body mass index, and length of hospital stay, did not differ significantly among surgical types. Conclusion: Laparoscopically assisted surgery for adnexal tumors via a single suprapubic incision under epidural anesthesia is feasible and safe, and should be viewed as an alternative approach to conventional minimally invasive surgery.